Formation of an Ethical Communication Culture (Pragmatic Studies) - Dedy Arif Norwahyudi; Ade Hanafi Al fatih (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
This study aims to analyze the formation of ethical communication culture through a pragmatic approach. Ethical communication culture is very important in social interaction because it plays a role in building harmonious relationships and mutual respect. Using a qualitative method, this study examines the various forms and principles of ethical communication applied in society as well as how pragmatic norms and values influence communication behavior. The results show that ethical communication is formed through pragmatic awareness, namely understanding of context, language adjustment, and politeness in speaking. In addition, social and cultural factors also play a role in shaping ethical communication patterns. This study contributes to the understanding of the importance of pragmatics in creating an ethical communication culture and can be applied in various contexts of social interaction.